1994
DOI: 10.1159/000110365
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Japanese Encephalitis

Abstract: Over a 5-year period, virological investigations for Japanese encephalitis (JE) were conducted in children presenting with acute encephalopathic illness. Clinical features of JE-positive patients (n = 116) were compared with patients in whom the diagnosis could be excluded (n = 57). Multivariate analysis by logistic regression revealed that two clinical signs – central hyperpneic breathing pattern and extrapyramidal signs – were significant predictors of the diagnosis. Application of the model yielded a sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 5 publications
1
59
0
Order By: Relevance
“…9,[11][12][13][14][15][16] In our study, however, we found that rates with any neurological sequelae and mental disorders among adult ( 15 years old) JE cases was similar to that in the young (2-5 and 6-14 years groups) JE cases. Differences of our results from other studies in disability rates may be due to whether the formal examination has been used or the number of surviving JE cases has been surveyed.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…9,[11][12][13][14][15][16] In our study, however, we found that rates with any neurological sequelae and mental disorders among adult ( 15 years old) JE cases was similar to that in the young (2-5 and 6-14 years groups) JE cases. Differences of our results from other studies in disability rates may be due to whether the formal examination has been used or the number of surviving JE cases has been surveyed.…”
Section: Discussionmentioning
confidence: 60%
“…The survivors' disability rate was similar to survivor disability rates seen in India and Vietnam (45.5-58.0%). 11,12 We found that motor neuron symptoms were paralysis, hemiplegia, and limb movement disorder such as reduced muscle strength, tendon reflexes, involuntary movements, increased muscle tone, and sensory dysfunction were the most common neurological sequelae for JE cases. Rates of neurological sequelae were very high at discharge and showed no apparent improvement with 1-2 years after discharge.…”
Section: Discussionmentioning
confidence: 98%
“…Two clinical signs, namely hyperventilation in the acute stage and extrapyramidal features, were significantly and independently associated with a diagnosis of JE. 68 JE is now also recognized to involve spinal cord anterior horn cells and occasionally present with lower motor neurone polio-like weakness with atrophy. 69,70 The polio-like illness may occur with a normal level of consciousness or with coma.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Motor paralyses including hemiplegia and tetraplegia may also be present. Signs of extra pyramidal involvement, including tremor, rigidity, and abnormal movements are observed in around 30% of the patients (Kumar et al, 1994). Severe clinical cases are likely to have life-long neurological sequelae.…”
Section: Clinical Manifestationsmentioning
confidence: 99%